EFEKTIVITAS MEDIA PEMBELAJARAN IPA DALAM MENGEMBANGKAN ENVIRONMENT AWARENESS SISWA SEKOLAH DASAR - Anjani, Tarisa; Angger Wardhani, Prayuningtyas; Fahrurrozi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Environmental degradation calls for ecological awareness from an early age; however, conventional science education in elementary schools ultimately fails to foster meaningful conservation behaviors. This study examines the effectiveness of science learning materials in developing students’ environmental ecological awareness, identifies dominant indicators, and maps current research trends and gaps. Using the Systematic Literature Review (SLR) method with the PRISMA protocol, data were synthesized from scientific articles published between 2022 and 2026. Findings indicate that science learning media consist of three typologies: immersive digital media (digital comics and Virtual Reality), concrete project-based tools (STEAM), and art-integration media (SDGs performances). Digital innovations have been shown to enhance cognitive retention through interactive simulations, while concrete projects and artistic expression strongly stimulate students’ affective and psychomotor domains through real-world actions such as recycling and waste reduction. Research trends are shifting toward immersive, experience-based learning, although gaps regarding the integration of blended media and the consistency of long-term behavior remain. These insights serve as a guide for educators in designing contextual science media.